Implementation of management of performance of educators in the Department of Education in Waterberg District of Limpopo Province - Mabitsi, Matome Thomas (My University, 2009)
The mini-dissertation takes off by studying the phenomenon of the management of performance of human resources in the Department of Education in Limpopo Province by specifically looking at practice of educators and managers in Waterberg District and how they implement the management of performance of educators in that District. Chapter one introduced the reader to the central concerns and issues raised in the mini-dissertation. For many years the Department of Education had attempted to implement a performance management system without success and without knowing what were the factors that made such an implementation not succeed and if it succeeded in some ways why it did not succeed to the desired extend. This chapter revealed that the aim of the study was to investigate factors that inhibited the implementation of management of performance of educators and that the research aimed at making recommendations for the successful implementation of the management of performance. Chapter two was aggressive in bringing a league of distinguished scholars who brought as many angles to the phenomenon as they understood and studied it. It brought together relevant and useful literature to the topic under study. Chapter three outlined to the reader the design of the research as well as the methodology that was used to bring about the realities of the implementation of the management of performance of educators. In order to increase the reliability of the findings a number of methodologies were triangulated. Chapter four was instrumental in analyzing the data and arriving at a scientific truth about what are the factors that affected the implementation of the management of performance of educators in the Department of Education in Limpopo Province. It is remarkable to note from the analysis of this data the high percentage of educators who are in the Department and are disillusioned by the prospects of a successful implementation of the management of performance of educators. Chapter five made far reaching conclusions and recommendations about what needs to be done in order to have the management of performance of educators successfully implemented.
Thesis (MPA.) -- University of Limpopo, 2009
Keywords: Performance management; Human resources; Department of Education; Educators; School personnel management -- South Africa; Teacher effectiveness -- South Africa